An “acquired” hemoglobin J variant in a sickle cell disease patient - Nawwar Swedan; Kathleen Nicol; Phylis Moder; Samir Kahwash (Dove Medical Press, 2008)
Nawwar Swedan1, Kathleen Nicol2, Phylis Moder2, Samir Kahwash21Fellow in Transfusion Medicine, Ohio State University, Columbus, Ohio; 2Department of Laboratory Medicine, Nationwide Children’s Hospital, Columbus, OhioAbstract: We report the case of a rare hemoglobin variant, “Hemoglobin J”, discovered while performing hemoglobin electrophoresis following exchange transfusion of a sickle cell disease patient. It is usual practice in our institution to confirm the hemoglobin S level in sickle cell disease patients after red cell exchange. The patient had received 5 red cell units and the source of this variant was traced back to two of those units. Due to the uncertain clinical impact of this variant, and the lack of specific guidelines, the two donors were deferred from future donations to our institution.Keywords: hemoglobin J, sickle cell disease, transfusion